Efficiency Enhancement of Inverted Polymer Solar Cells Using Ionic Liquid-functionalized Carbon Nanoparticles-modified ZnO as Electron Selective Layer - Zhu, Feng; Chen, Xiaohong; Lu, Zhe; Yang, Jiaxiang; Huang, Sumei; Sun, Zhuo (Nano-Micro Letters, 2013)
ZnO thin film was fabricated on tin-doped indium oxide electrode as an electron selective layer of inverted polymer solar cells using magnetron sputtering deposition. Ionic liquid-functionalized carbon nanoparticles (ILCNs) film was further deposited onto ZnO surfaces by drop-casting ILCNs solution to improve interface properties. The power conversion efficiency (PCE) of inverted polymer solar cells (PSCs) with only ZnO layer was quickly decreased from 2.7% to 2.2% when the thickness of ZnO layer was increased from 15 nm to 60 nm. However, the average PCE of inverted PSCs with ZnO layer modified with ILCNs only decreased from 3.5% to 3.4%, which is comparable to that of traditional PSCs with poly(3,4-ethylenedioxythiophene)/poly(styrenesulfonate) anode buffer layer. The results suggested that the contact barrier between ZnO layer and poly(3-hexylthiophene) and phenyl-C61-butyric acid methylester (P3HT:PCBM) blended film compared to ZnO bulk resistance can more significantly influence the performance of inverted PSCs with sputtered ZnO layer. The vanishment of negative capacitive behavior of inverted PSCs with ILCNs modified ZnO layer indicated ILCNs can greatly decrease the contact barrier of ZnO/P3HT:PCBM interface.